Uruguay and the 21st century surgery. New challenges from old ideas… - Ruso Martínez, Luis (Cirugía del Uruguay, 2019)
The history of surgery practically begins about 150 years ago. The foregoing is the darkness of ignorance; only in 1543 the anatomy comes out of the galenic concepts and 100 later Harvey describes the blood circulation, surely inspired by the ideas of Descartes ...